NC 4.0, a Novel Approach to Nonconformities Management: Prioritizing Events With Risk Management Tools - Ravoy, Dvir; Parmet, Yisrael (Frontiers in Artificial Intelligence, 2021)
Quality 4.0, the correspondent quality practices fit to address the Industry 4.0 mindset, is expected to provide models and processes endorsed by continuous improvement and data driven proofs especially given the exponential growth in available data. The research consolidates the reality of big data availability (part of quality 4.0) with a generic aspect of quality – managing nonconformities. Its purpose is to suggest a model to improve the initiation step for dealing with a nonconformity by prioritizing these events. The new concept in the model suggested is incorporating the risk management method of prioritizing into the nonconformity’s management. These tools are designed to transform qualitative data into quantitative one and enable easier decisions making, in this case choosing which issue to deal with first. The research approach is developing and testing the suggested model as a pilot in a real production environment to establish its impact and define key guidelines for utilizing it in various processes. In addition, conduct a survey among quality experts from different organizations for reference. Two main outcomes were achieved during the research: The quality experts survey welcomed the model concept as a structured tool based on the solid risk management methodology. Implementing the model on actual production lines resulted in a significant reduction of NC financial impact as the events were solved per their impact.